Beowulf : a translation and commentary : together with Sellic spell - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Tolkien, Christopher; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. (Boston, MA : Houghton Mifflin Harcourt, 2014)
From his creative attention to detail in these lectures there arises a sense of the immediacy and clarity of his vision. It is as if he entered into the imagined past: standing beside Beowulf and his men shaking out their mail shirts as they beached their ship on the coast of Denmark, listening to the rising anger of Beowulf at the taunting of Unferth, or looking up in amazement at Grendel's terrible hand set under the roof of Heorot.
But the commentary in this book includes also much from those lectures in which, while always anchored in the text, he expressed his wider perceptions. He looks closely at the dragon that would slay Beowulf "snuffling in baffled rage and injured greed when he discovers the theft of the cup"; but he rebuts the notion that this is "a mere treasure story", "just another dragon tale". He turns to the lines that tell of the burying of the golden things long ago, and observes that it is "the feeling for the treasure itself, this sad history" that raises it to another level. "The whole thing is sombre, tragic, sinister, curiously real. The 'treasure' is not just some lucky wealth that will enable the finder to have a good time, or marry the princess. It is laden with history, leading back into the dark heathen ages beyond the memory of song, but not beyond the reach of imagination."
Introduction to the translation -- Beowulf -- Notes on the text of the translation -- Introductory notes to the commentary -- Commentary -- Sellic Spell -- The lay of Beowulf.
Text in English.
Includes bibliographical references.
Keywords: Beowulf; Epic poetry, English (Old); Monsters -- Poetry; Dragons -- Poetry; Beowulf; Dragons; Epic poetry, English (Old); Monsters; Poetry